2014
DOI: 10.2752/175303714x13837396326251
|View full text |Cite
|
Sign up to set email alerts
|

Animal-Assisted Interventions in Children's Hospitals: A Critical Review of the Literature

Abstract: There is a perception in the scientific and general communities that hospitalized children benefit from visits by animals. Animal-assisted interventions (AAI), including animal-assisted therapy and animal-assisted activities, usually involving dogs, are thus employed in pediatric hospitals. However, the actual prevalence of AAI in children's hospitals has been poorly documented in the literature. Furthermore, the evidence base for claims that children in hospital benefit from AAI is limited. There are nine exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 39 publications
(55 reference statements)
0
59
0
5
Order By: Relevance
“…It also poses specific challenges to the evaluation and comparison of such studies. More comprehensive discussions of the (methodological) difficulties that are frequently involved in conducting research on animal-assisted interventions can be found in other reviews (e.g., Johnson, Odendaal, & Meadows, 2002;Stern & Chur-Hansen, 2013;Chur-Hansen, McArthur, Winefield, Hanieh, & Hazel, 2014). In the following sections, only a few general issues and practical considerations regarding human-animal interactions will be discussed that should be taken into account when deciding on the application of or conducting research involving animal-assisted interventions.…”
Section: Practical Considerations In Animal-assisted Intervention Resmentioning
confidence: 99%
“…It also poses specific challenges to the evaluation and comparison of such studies. More comprehensive discussions of the (methodological) difficulties that are frequently involved in conducting research on animal-assisted interventions can be found in other reviews (e.g., Johnson, Odendaal, & Meadows, 2002;Stern & Chur-Hansen, 2013;Chur-Hansen, McArthur, Winefield, Hanieh, & Hazel, 2014). In the following sections, only a few general issues and practical considerations regarding human-animal interactions will be discussed that should be taken into account when deciding on the application of or conducting research involving animal-assisted interventions.…”
Section: Practical Considerations In Animal-assisted Intervention Resmentioning
confidence: 99%
“…Entretanto, como referido em estudo de revisão sobre a temática (2) , é importante destacar que são escassas as pesquisas utilizando IAA.…”
Section: Discussionunclassified
“…Estudos recentes têm reconhecido os potenciais benefícios para a saúde e o bem-estar de crianças hospitalizadas, decorrentes de atividades como visita de animais, favorecendo um ambiente com menos tensão, estreitando relações interpessoais entre crianças, familiares e equipe, melhorada auto-estima, distração, prazer e incremento nas habilidades sociais (1)(2)(3)(4) . Apesar da literatura limitada sobre a evidência, especificamente no Brasil, essas intervenções vêm sendo incorporadas, em diversos contextos de saúde, tais como:…”
Section: Introductionunclassified
“…Optimally, a consistent AAI treatment protocol would be helpful for the purposes of research to examine what, in these sessions, may be most beneficial and/or detrimental for people and for therapy animals (Chur-Hansen et al, 2014). Optimally, a consistent AAI treatment protocol would be helpful for the purposes of research to examine what, in these sessions, may be most beneficial and/or detrimental for people and for therapy animals (Chur-Hansen et al, 2014).…”
Section: Defining An Aai Protocol In Pediatric Oncology Settingsmentioning
confidence: 99%